Luxación de rótula en el perro: ¿Vale todo para resolverlo? - Montenegro Martínez, Isabel; Gutiérrez Velasco, Daniel; Martín Cebrián, Eva (Revista Complutense de Ciencias Veterinarias, 2007)
Sin resumen